A comparative study of the school broadcasts in the Philippines and in Thailand - Chaluay Ruangchan 1944- (Quezon City University of the Philippines Diliman, 1968)
The purpose of the study is to compare the school broadcast programs in the Philippines and in Thailand, particularly in the historical background, organization and administration, programming and scheduling, and financing, and to point out the problems they encountered. To gather data and make the comparison, historical and descriptive approach were used. Data were obtained from records, reports, and other documents on the school broadcasts in the two countries.
Includes curriculum vitae
Thesis
Keywords: Radio in education -- Philippines; Radio Broadcasting; Radio in education -- Thailand